Anniversary meeting: 30 November 1891 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1892)
At the anniversary meeting new Fellows were elected and a list of Fellows who died during the previous session was read. Meeting notes for 14 December, 1891 are appended.